PERBANDINGAN DISOLUSI ASAM MEFENAMAT DALAM SISTEM DISPERSI PADAT DENGAN PEG 6000 DAN PVP - yulias ninik; sugiyono sugiyono; widhi astuti; maria faizatul (Universitas Wahid Hasyim Semarang, 2014)
ABSTRACT Mefenamic acid is an analgetic that insoluble in water, therefore several approaches are required to improve the dissolution and bioavailability. The aim of this research is to know the dissolution of mefenamic acid in solid dispersion system with PEG 6000 and PVP. Solid dispersion of mefenamic acid-PEG 6000 were prepared by fusion method and mefenamic acid-PVP by solvent evaporation method with contain PEG 6000 or PVP for FI (20%), FII (40%), FIII(60%), FIV (80%) and FV (100%) respectively were compared with the weight of mefenamic acid. The powder of solid dispersion systems were investigated for its recovery and dissolution in medium fosfat buffer pH 7.4 until 60 minutes. Pure mefenamic acid and the physical mixture with polimer were used as compared powders. The result of dissolution testing were revealed by Dissolution Efficiency (DE60). The result showed that both PEG 6000 and PVP can increased the dissolution of mefenamic acid from solid dispersion systems. The DE60 of mefenamic acid-PEG 6000 from FI 38,81%; FII 51,05%; FIII 62,87%; FIV 75,63%; FV 87,03%; and the physical mixture of FV 58,84% respectively. Meanwhile the DE60 mefenamic acid-PVP from FI 26,76%; FII 37,78%; FIII 45,23%; FIV 62,41%; FV 82,71%; and the physical mixture of FV 26,44% respectively. Keywords : mefenamic acid, PEG 6000, PVP, solid dispersion, dissolution